Donation or Advertising? The Role of Market and Non-market Strategies in Corporate Legitimacy - Liu, Ying; Liu, Wei; Xu, Yingbo (Frontiers in Psychology, 2022)
Although existing research has discussed the impact of market strategy or non-market strategy on corporate legitimacy thoroughly, there is limited research on the joint role of the two strategies. Based on the big data analysis of media coverage, this study addresses this research gap by using a sample of Chinese listed firms during 1999–2018. Our finding reveals that positive media coverage promotes corporate financial performance, and advertising intensity and corporate donation strengthen this relationship. However, the simultaneous application of market and non-market strategies diminishes the effect of both strategies on the expansion of corporate legitimacy. This study extends the literature on the impact of corporate strategies on corporate legitimacy by highlighting the joint role of the corporate market and non-market strategies.